Potential ectoparasiticide for dog and cat fleas, a combination of Ficus minahassae extract and latex from Carica papaya L. (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to analyze the compound content of the combined extracts of Langusei fruit (Ficus minahassae L.) and papaya latex (Carica papaya L.) and perform bioassays of the combination of extracts on fleas of the genus Ctenocephalides. Materials and Methods: Liquid chromatography-tandem mass spectrometry (LC-MS/MS) determined the chemical composition of the combined extract. The toxicity of the extract combination was evaluated in vivo on cat flea and dog flea imago separately. The combination of phytochemical screening of Langusei extract and papaya latex contained all the main phytochemical compounds. Results: The LCMS/MS analysis results showed that the combination of Langusei extract and papaya latex contained six compounds. Four compounds were identified: 3-butenyl glucosinolate, erythromycin, aluminum palmitate, and henpentakontilbenzene. Four compounds indicate a new compound. The toxicity of the combined extract was highest for both Ctenocephalides felis and Ctenocephalides canis in the P4 treatment (10%), with an average mortality of 100%, the same as the control mortality of the synthetic insecticide deltamethrin. The best LD50 for C. felis was in the F1 formula (4.003 mg/l), while in C. canis it was shown in the F3 (3.733 mg/l). Conclusion: Based on the results obtained, the combination of Langusei fruit extract and papaya latex can be developed as an ectoparasiticide for fleas of the genus Ctenocephalides.J. Adv. Vet. Anim. Res., 11(3): 810–818, September 2024http://doi.org/10.5455/javar.2024.k833